Kesenjangan UMKM pada Pengelolaan Keuangan: Studi di Kota Jambi - Titin Agustin Nengsih; Mohammad Orinaldi; Yudha Nurwahid (Universitas Batanghari Jambi, 2022)
The Micro, Small and Medium Enterprises (MSME) sector plays a significant role in advancing Indonesia's economic development, which is founded on the idea of people's economic development. Even for tiny organizations, financial management analysis can have a significant impact on overall business success. However, the majority of small firms lack expertise of financial management, particularly financial management, and do not recognize the value of bookkeeping and documentation for maintaining business continuity. MSME entrepreneurs think that really putting financial management into practice is more crucial. Therefore, the goal of this study is to investigate the financial management practices used by SMEs. This study employs descriptive qualitative research techniques to conduct a field survey. The small and medium-sized businesses in Jambi City's Alam Barajo District are the focus of this study. ways for gathering data, including documentation, interviews, and observation. According to the survey's findings, there is still a lack of knowledge among MSME actors in Jambi City's Alam Barajo District regarding financial management. The actors in MSME organizations' ignorance is playing a bigger role in the implementation of this financial management. When it comes to financial management, MSME players are seen using financial management. The four theoretical indicators of financial management are control, recording, reporting, and budget use. The most typical method employed by MSME actors is budget tracking. Reporting and management metrics are infrequently employed by MSME owners.